The Challenges of Rural-Urban Migration In Developing Countries (Tanzania Journal for Population studies and Development, 2013)
Migration is the movement of people from one geographical location to another, involving permanent or temporary settlement. One noticeable aspect in the society today is the rate at which people migrate from rural to the centres. While urban centres are increasing in population, rural areas are decreasing in population. For these reasons, there is a widespread concern that the rates of rural-urban migration should be slowed. But more importantly to policy makers is that urban unemployment and high rates of urbanization pose strong social and political challenges for reducing the flow of migrants to urban areas. This paper discusses the challenges that face rural-urban migration. It analyzes migration theories that provide theoretical reasoning behind rural-urban migration. This paper draws from the empirical literature review of studies on rural-urban migration through collection of secondary data and reviewing information that has been gathered from various studies and reports in research and academic institutions, as well as from internet sources in and outside Tanzania.